Vegetation growth impacts conveyance efficiency of irrigation canals - a geo-drone approach - Kulkarni, A. A.; Nagarajan, R. (International Journal of Engineering and Technology, 2018)
In spite of canals are most important conveyance systems for delivering water for irrigation in the alluvial plains of India, many irrigation canal projects are suffering from massive growth aquatic plants along the canal sides known as aquatic weeds and siltation along canal bed. Aquatic weeds are unwanted plants playing a very important role in different eco-systems and many of them cause enormous direct and indirect losses. The losses include interference with the cultivation of crops, loss of biodiversity, loss of potentially productive lands, loss of grazing areas and livestock production, erosion following fires in heavily invaded areas, choking of navigational and irrigation canals and reduction of available water in water bodies. Also, it has been found that it severely reduces the flow capacity of irrigation canals thereby reducing the availability of water to the farmers. The vegetation on bottom and sides of the canal increases the roughness resulted into a decrease in velocity which further leads to silt deposition on canal bed which affects the canal functions. The complexity of these situations has resulted in a need for identification of impact of weeds on the hydraulic efficiency of canals. For accurate identification of weeds, low altitude drone survey becomes an innovative solution than other conventional methods. This study captured vegetation along the canal using the drone images and estimated roughness shows, the reduction in conveyance efficiency by 21.90% compared with design data.